(untitled) (Research, Society and Development, 2021)
This study aims to raise a Clinical-epidemiological focus on Covid-19 in cancer patients. The present study used the integrative review as a methodological research approach. The following guiding question was chosen: "What are the main clinical signs in cancer patients with Covid-19?" and “What is the epidemiology of cancer together with covid-19?”. To carry out this study, the following databases were consulted: MEDLINE, Scholar Google, LILACS, SCIELO and Repositories. The Health Sciences Descriptors (DeCS) were used in an associated way: COVID-19, Cancer, Epidemiology, Clinical and Coronavirus. Initially, 165 articles were found. Of these, 82 were selected for full reading. Discordant cases were deliberated by consensus, resulting in the final selection of 12 articles for full reading and preparation of this study, which contained clinical and epidemiological information on cancer patients who were infected by the new coronavirus. People with advanced age and those with chronic illnesses such as diabetes, cardiovascular and respiratory diseases, and with low immunity, are at greater risk of having serious complications if they are contaminated by the coronavirus. Likewise, people with cancer who are undergoing chemotherapy treatments, radiotherapy, who have undergone surgery for less than a month or who use immunosuppressive drugs are part of the risk group, considering that cancer patients are effectively more vulnerable to develop COVID-19 at its most severe.